Application of Geographic Information Systems (GIS) for the classification of production systems and determination of grazing pressure in uplands of the Awash River Basin, Ethiopia - Bizuwork, A.; Tadddesse, G.; Peden, Donald G.; Jobre, Y.; Getahun, Y. (2006)
Expansion of cultivation and settlements has increasingly grown in most part of the uplands of Awash river basin. This expansion has exerted pressure on the existing grazing lands and forests. It is, therefore, a paramount importance to identify suitable land for various uses in optimum utilization while causing minimum impact to the environment. In this study, classification of productive system of the existing land and determination of the grazing pressure was made by incorporating different spatial information using GIS techniques. The result showed that about 70% of the total land is suitable for rainfed mixed farming system. 9% for irrigated mixed farming systems. 125% for grassland based systems and the remaining 9% for forest land. The amount of dry matter yield (DM) that can be produced from the land ranges from 591.85 to 2473.72 kg/ha/year. The total DM value expected would be 301362 ton/year.